The application of tissue engineering in degenerative disc disease: an Islamic perspective - Mohamad, Mohd Yusof; Zainuddin, Zainul Ibrahim; Sha'ban, Munirah (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2014)
Discussions pertaining to the application of Tissue Engineering in general, and more specifically, in degenerative disc disease from Islamic perspectives have yet to gain the necessary attention in literature. This paper serves to address that gap. Primarily, the deliberations took into account the role of Tissue Engineering in meeting the principles and objectives of the present healthcare scenario. It begins with an overview of Tissue Engineering, leading to the understanding of Regenerative Medicine. Special emphasis is given to discussions pertaining to the tissue engineering principles, and their characteristics, that are used in this technology. These are followed by brief discussions of four Islamic perspectives, namely; Concept of the Islamic Worldview, principles (Qawa‟id) and objectives (Maqasid) of the Shari‟ah and Islamic Jurisprudence. Attempts were made to align Tissue Engineering with respect to those Islamic perspectives. These efforts were undertaken to address some concerns with respect to Islamic viewpoints pertaining to the application of the technology in Muslim individuals. The paper distances itself from providing an ultimate Islamic decree in the application of Tissue Engineering in healthcare. The work could provide some foundations for Islamic theologians to formulate a decree to the effect. It is also hoped that the highlighted areas can provide some insights and further deliberations towards the understanding of the technology in relation to what Islam champions.